The Economic Cost of Sexual and Gender-Based Violence -Evidence from Jaffna District during the Socio-Economic Crisis - Suveedda, P. (University of Jaffna, 2022)
Sexual and Gender-Based violence is a crucial human rights issue that occurred gender-based unequal power relations and mostly victimized women and girls all over the world. It includes physical, emotional, psychological, and sexual violence and Millions of women have died and are disabled globally. Violence makes economic and social costs in terms of job loss, poverty, lack of access to resources and services, and inequality because violence denies education, political participation, social engagement, and employment. Prevailing economic and social crises induce the above incidence in various forms in Sri Lanka and analyze this problem, Jaffna District has been selected as a research area. To find out the result of this study, qualitative research methods such as structured interviews with key persons and discussions with responsible groups have been adopted. The results show that the SGBV has increased drastically by causing several socio-economic factors during the economic crisis in a particular area and it affects women’s well-being negatively in order to make economic costs immensely. Therefore, the government and respective organizations should be aware of this threatening issue and undertake suitable strategies to prevent violence against women.
Keywords: Crisis; Economic costs; SGBV; Women